A COMPARATIVE ANALYSIS OF POSSESSIVE PRONOUNS IN ENGLISH AND RUSSIAN LANGUAGES - Tinishova Gulruh; Aziz Mukhamadiev (Лучшие интеллектуальные исследования, 2024)
`Annotation: Possessive pronouns are pronouns that show ownership or possession. They indicate that something belongs to someone or something. Possessive pronouns include words like "mine," "yours," "his," "hers," "ours," and "theirs." These pronouns are used to replace nouns to show that someone or something possesses or owns something. They replace nouns or noun phrases that show possession, making sentences more concise and avoiding repetition. This thesis aims to delve into the similarities and differences between possessive pronouns in English and Russian languages.